THU0118 Sequential ep1 and ep4 regulation in a rabbit model of antigen-induced arthritis. (1st June 2001) - Diez-Ortego, I; Largo, R; Sanchez-Pernaute, O; Guerrero, R; Lopez-Armada, MJ; Palacios, I; Egido, J; Herrero-Beaumont, G
Abstract : Background: Prostaglandin E2 (PGE2) exerts its actions through the binding of the high affinity receptors EP. There are 4 isoforms of EP receptors with extracellular domains highly conserved, each coupling different intracellular transduction systems. Distribution of EP subtypes in the target tissues is therefore central to the pathways elicited by PGE2. Objectives: The aim of this work was to study the regulation of EP1 and EP4 receptors in the inflamed synovial tissue. Methods: We have studied different time periods in a rabbit model of antigen-induced arthritis: 24, 48 and 72 h (acute phase) and 1, 2 and 3 weeks (chronic phase). Knee synovial fluid (SF) volume and white cell count were measured. Total RNA was extracted from the synovial membranes and expression of EP1 and EP4 receptors was studied by RT-PCR techniques. A fraction of synovial tissue was fixed and embedded in paraffin for morphological studies. Results: At the acute stages of the disease the animals depicted a synovial effusion that peaked at 48 h. The highest white cell infiltration was found at 24 h and was dominated by neuthophils; at 72 h neutrophils and mononuclear cells showed similar concentrations in the SF. Al longer time-periods only half of the cases showed a synovial effusion, of smaller proportion. The acute histopathologic lesions consisted of leakage of plasma elements with prominent neutrophil invasion. At 72 h lining hyperplasia developed and there was a switch to mononuclear cell infiltration at the subintima. At further stages, fibrotic changes and increases vascularisation were also found. EP1 receptor expression was up-regulated at every point of study, when compared to controls. EP1 expression increased in a time dependent fashion, peaking at 2 weeks (14-fold vs. control). On the other hand, healthy controls expressed moderate EP4 levels, which were dramatically reduced at the acute stage of the disease (90% reduction at 72 h). At the latest periods studied, there was a normalisation and even slight up-regulation of EP4 expression. Conclusion: Our data may suggest that EP1 receptor mediates some of the PGE2 actions in experimental arthritis. This actions do not only include plasma leakage and activation of early inflammatory mediators, as EP1 up-regulation continues to increse when these typical features of acute arthritis are no longer evident. EP4 down-regulation at the early stages of the disease may suggest that this molecule do not participate in oedema and neutrophil activation induced by PGE2 in this experimental model. Restoring of the balance between PGE2 receptors in arthritis could be of help for the control of the inflammatory reaction.